Homometallic Ln(iii)-complexes from an ILCT ligand with sensitized vis-NIR emission, excitation-dependent PL color tuning and white-light emission. Issue 13 (15th March 2018) - Liao, Wei-Ming; Li, Chao-Jie; Wu, Xiangwen; Zhang, Jian-Hua; Wang, Zheng; Wang, Hai-Ping; Fan, Ya-Nan; Pan, Mei; Su, Cheng-Yong
Abstract : Homometallic Ln(iii )-complexes with sensitized vis-NIR emission and excitation-dependent PL color tuning were achieved from an ILCT ligand. Abstract : A facilely available zwitterionic ligand, 1, 1′-(1, 4-phenylenebis(methylene))dipyridin-4(1 H )-one (PBPO), has been designed to bear intraligand charge transfer (ILCT) energy states. PBPO was used to assemble two series of Ln(iii ) complexes with either 2D (6, 3)-hcb network (LIFM-24 (Ln), Ln = Pr, Nd, and Sm), or 1D loop-and-chain (LIFM-25 (Ln), Ln = Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb) polymeric structures, as determined by the radius of the lanthanide ions. Highly efficient photoluminescence (PL) in the visible to near-infrared (NIR) regions can be obtained in these Ln-complexes, due to the extended energy transfer from both the triplet and ILCT states of the zwitterionic ligand. Among these complexes, LIFM-24 (Pr) andLIFM-25 (Dy) display excitation-dependent color tunable luminescence and white-light emission based on the combination of ligand-centered (LC) and metallic-centered (MC) emissions. Uniquely, a strict linear relationship was established between the excitation wavelength and the emission CIE (Commission Internationale de L'Eclairage) coordinates in a wide color range (orange to blue forLIFM-24 (Pr), and yellow to blue forLIFM-25 (Dy)), thereby providing prototype models for programmable PL color tuning and white-light emission, which are rarely achievable in homometallic Ln-complexes.